2021
DOI: 10.33005/mebis.v5i2.146
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kepemilikan Manajerial Memoderasi Pengaruh Keputusan Keuangan Terhadap Nilai Perusahaan Manufaktur Di Bursa Efek Indonesia

Abstract: Nilai perusahaan adalah hal yang sangat penting, karena mencerminkan kinerja perusahaan yang dapat berpengaruh terhadap persepsi investor kepada perusahaan. Penelitian ini memiliki tujuan untuk mengetahui, menguji, dan membuktikan secara empiris dari (1) pengaruh keputusan investasi terhadap nilai perusahaan, (2) pengaruh keputusan pendanaan terhadap nilai perusahaan, (3) pengaruh kepemilikan manajerial dalam memoderasi hubungan keputusan investasi terhadap nilai perusahaan, (4) pengaruh kepemilikan manajerial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
3
3
0
1
Order By: Relevance
“…Signaling theory explains how managerial ownership can act as a mechanism that amplifies positive signals sent by a company through investment decisions, which in turn can influence market perceptions and company value (Astika & Suryandari, 2019). This finding is consistent with research conducted by Rachmah & Iswara (2023), Arianti & Anwar (2020), .…”
Section: Mediation Effects Of Managerial Ownership On Investment Deci...supporting
confidence: 85%
See 1 more Smart Citation
“…Signaling theory explains how managerial ownership can act as a mechanism that amplifies positive signals sent by a company through investment decisions, which in turn can influence market perceptions and company value (Astika & Suryandari, 2019). This finding is consistent with research conducted by Rachmah & Iswara (2023), Arianti & Anwar (2020), .…”
Section: Mediation Effects Of Managerial Ownership On Investment Deci...supporting
confidence: 85%
“…This suggests that managerial ownership plays a mediating role in the relationship between investment decisions and firm value. Making appropriate investment decisions can improve a company's value, benefiting shareholders, including management who holds shares in the company (Arianti & Anwar, 2020). Therefore, managers share the same interests as other shareholders in increasing the company's value.…”
Section: Mediation Effects Of Managerial Ownership On Investment Deci...mentioning
confidence: 99%
“…This is supported by the research of Suta et al (2016) and A. Ayu et al (2020) and Arianti & Anwar (2020), Reksita Sari (2018) and Mubaraq et al (2020) which show that the implementation of good corporate governance will motivate management to provide decisions that are following investor expectations. H3: GCG significantly moderates the relationship between investment decisions to company value.…”
Section: Good Corporate Governance (Gcg)mentioning
confidence: 78%
“…Manufacturing companies in In Indonesia, several studies have demonstrated the significant impact of institutional ownership on a company's financial performance. Notably, research conducted by (Sari & Rahmawati, 2018) found a positive relationship between institutional ownership and a company's profitability. This connection can be attributed to the improved access to company information and substantial financial support that financial institutions like banks, insurance companies, and pension funds can provide (Wirawan & Widiastuti, 2019).…”
Section: Introductionmentioning
confidence: 99%